Variasi Morfologi Sukun Artocarpus altilis (Park.) Forsberg Di Kota Bekasi - Angga Rahabistara Sumadji; Leo Eladisa Ganjari; Christianto Adhy Nugroho; Endang Purwaningsih (Universitas Nusantara PGRI Kediri, 2022)
Breadfruit is one type of versatile plant that is of economic value because itproduces fruit with a fairly high nutritional content. Breadfruit plants havediverse morphological variations, so their morphological variations can be usedas a way to determine a type of breadfruit, especially whether the quality issuperior or not. This study aims to determine the morphological variations ofbreadfruit plants (Artocarpus altilis (Parkinson) Forsberg) originating fromvillages in Bekasi City. The stages of this study include observation andobservation of morphological characters ranging from trees, leaves, flowers andfruits. Breadfruit plants in Bekasi city have an average height of ±11.5 m, withthe highest breadfruit plants reaching 12.90 m and the lowest 7.9 m, the largestbreadfruit stem circumference is 125 cm and the smallest is 98.5 cm, thelargest breadfruit canopy diameter is 4.67 m and the smallest is 6.14 m, theshape of the canopy of the Breadfruit plant in Bekasi city is irregular, pyramidsand pyramids are broad, the leaves of the Breadfruit plant in Bekasi city, ingeneral, have the same shape, namely dark green, rhombus-shaped withpinnate leaf bones, tapered leaf tips and leaf edges are enamelled, the maleflowers of Breadfruit are in the form of a whole with a diameter of up to 5 cmand a length of 45 cm consisting of many individual flowers, tubular flowerscontaining a single stamen with two anthers on thick filaments, male and femaleflowers on breadfruit plants are separated in the same plant, the morphology ofbreadfruit in the city of Bekasi has the characteristics of a rounded shape, thesurface of the skin of the fruit is prickly, if palpable it feels rough, as well aswhite fruit flesh.